Mechanism-based model of parasite growth and dihydroartemisinin pharmacodynamics in murine malaria - Patel, K.; Batty, Kevin; Moore, Brioni; Gibbons, P.; Bulitta, J.; Kirkpatrick, C. (American Society for Microbiology, 2013)
Murine models are used to study erythrocytic stages of malaria infection, because parasite morphology and development are comparable to those in human malaria infections. Mechanism-based pharmacokinetic-pharmacodynamic (PK-PD) models for antimalarials are scarce, despite their potential to optimize antimalarial combination therapy. The aim of this study was to develop a mechanism-based growth model (MBGM) for Plasmodium berghei and then characterize the parasiticidal effect of dihydroartemisinin (DHA) in murine malaria (MBGM-PK-PD). Stage-specific (ring, early trophozoite, late trophozoite, and schizont) parasite density data from Swiss mice inoculated with Plasmodium berghei were used for model development in S-ADAPT. A single dose of intraperitoneal DHA (10 to 100 mg/kg) or vehicle was administered 56 h postinoculation. The MBGM explicitly reflected all four erythrocytic stages of the 24-hour P. berghei life cycle. Merozoite invasion of erythrocytes was described by a first-order process that declined with increasing parasitemia. An efflux pathway with subsequent return was additionally required to describe the schizont data, thus representing parasite sequestration or trapping in the microvasculature, with a return to circulation. A 1-compartment model with zero-order absorption described the PK of DHA, with an estimated clearance and distribution volume of 1.95 liters h_1 and 0.851 liter, respectively. Parasite killing was described by a turnover model, with DHA inhibiting the production of physiological intermediates (IC50, 1.46 ng/ml). Overall, the MBGM-PK-PD described the rise in parasitemia, the nadir following DHA dosing, and subsequent parasite resurgence. This novel model is a promising tool for studying malaria infections, identifying the stage specificity of antimalarials, and providing insight into antimalarial treatment strategies.